PENGARUH MEDIA PEMBELAJARAN ADOBE FLASH TERHADAP HASIL BELAJAR MATA KULIAH STATIKA DI JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNP - 2100-2105, Ibrahim Ikhsan SM (CIVED, 2018)
Abstract— This research departs from the increasing value of low category students and lecturers still use the monotonous media in the statics lesson. The purpose of this research is (1) to reveal student learning result using Adobe Flash animation media compared to students who do not use Adobe Flash media (2) to reveal percentage comparison and significance of Adobe Flash animation media in learning result of the Statics course. The research method used is Quasi-Experimental Research, with the research design Nonequivalent Control Group Design. The research is done at the Department of Civil Engineering Faculty of Engineering, Padang State University. Data collection techniques are student learning outcomes based on the knowledge aspect. Data analysis technique is done by first doing normality test, homogeneity test and t-test. The results showed that the students' knowledge before being given the treatment of learning using Adobe Flash animation media, get the average learning outcome 56,7. After treatment the average value increased to 71,9. The percentage increase of student learning outcomes using Adobe Flash animated media obtained 26,8%. Hypothesis test using t-test get thitung> ttabel (3,689> 2,009) which shows that there is significant learning difference between classes using Adobe Flash animation media in Statics class of bar material with the class do not Adobe Flash animation using media.    Keywords: Learning Media, Adobe Flash Animation